Trends and hotspots in research on medical images with deep learning: a bibliometric analysis from 2013 to 2023 - Chen, Borui; Jin, Jing; Liu, Haichao; Yang, Zhengyu; Zhu, Haoming; Wang, Yu; Lin, Jianping; Wang, Shizhong; Chen, Shaoqing (Frontiers in Artificial Intelligence, 2023)
Background: With the rapid development of the internet, the improvement of computer capabilities, and the continuous advancement of algorithms, deep learning has developed rapidly in recent years and has been widely applied in many fields. Previous studies have shown that deep learning has an excellent performance in image processing, and deep learning-based medical image processing may help solve the difficulties faced by traditional medical image processing. This technology has attracted the attention of many scholars in the fields of computer science and medicine. This study mainly summarizes the knowledge structure of deep learning-based medical image processing research through bibliometric analysis and explores the research hotspots and possible development trends in this field. Methods: Retrieve the Web of Science Core Collection database using the search terms "deep learning", "medical image processing" and their synonyms. Use CiteSpace for visual analysis of authors, institutions, countries, keywords, co-cited references, co-cited authors, and co-cited journals. Results: The analysis was conducted on 562 highly cited papers retrieved from the database. The trend chart of the annual publication volume shows an upward trend. Pheng-Ann Heng, Hao Chen and Klaus Hermann Maier-Hein are among the active authors in this field. Chinese Academy of Sciences has the highest number of publications, while the institution with the highest centrality is Stanford University. The United States has the highest number of publications, followed by China. The most frequent keyword is "Deep Learning", and the highest centrality keyword is " Algorithm". The most cited author is Kaiming He, and the author with the highest centrality is Yoshua Bengio. Conclusions: The application of deep learning in medical image processing is becoming increasingly common, and there are many active authors, institutions and countries in this field. Current research in medical image processing mainly focuses on deep learning, convolutional neural networks, classification, diagnosis, segmentation, image, algorithm, and artificial intelligence. The research focus and trends are gradually shifting towards more complex and systematic directions, and deep learning technology will continue to play an important role.